CHARACTERISTICS OF PILI HEMAGLUTININ PROTEIN AND ITS ROLE IN THE PATHOGENESIS OF URINARY TRACT INFECTION WITH UROPATHOGENIC ESCHERICHIA COLI - Sudhana, I Wayan; Suwitra, Ketut; -, Sumarno (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
Urinary tract infection (UTI) is one of the most common infectious diseasesencountered in the community. The bacteria most frequently implicated as the causes ofUTI are the Gram-negative bacteria, especially Escherechia coli. Early phase of thepathogenesis of the infection constitutes adhesion of bacteria onto the epithelial cells ofurinary tract. SDS-PAGE examination was carried out to investigate molecule ofhemagglutinin protein and hemagglutination (HA) test continued by adhesion andinhibited adhesion tests.The observation of molecular weight of pili E. coli protein molecule byexplorative examination using SDS-PAGE showed on E. coli strip that the mostprominent molecular weights (MW) of the proteins were 61 kDa, 37 kDa, 30 kDa, and 20kDa. Purification by electro-elusion was done to proteins of the MW of 20 kDa, 37 kDaand 61 kDa. The HA test results indicated the 61 kDa, 37 kDa, and 20 kDa werehemagglutinin proteins and one which subsequently applied as sub unit proteins ofUropathogenic E. coli (UPEC) was the 37 kDa. Adhesion test of UPEC bacteria carriedout on urinary bladder epithelial cells of rabbit showed a significant correlation betweenadhesion index and various doses of subunit proteins of UPEC 37 kDa as coat of urinarybladder epithelial cells. Spearman rank correlation test and regression/non regressionanalysis confirmed an exponential decrease of UPEC adhesion to urinary tract epithelialcells as a response to the increasing doses of coating protein. This finding points out thatpili hemagglutinin protein subunit of UPEC 37 kDa was an adhesive molecule. Pilihemagglutinin protein subunit of UPEC 37 kDa is an adhesive molecule, which plays arole in adherence of UPEC to epithelial cells of urinary bladder at the early pathogenesisof urinary tract infection.
Keywords: Uropathogenic Escherichia coli, molecule of hemagglutinin protein, adhesive index, urinary tract infection